The Role of Transformational Leadership and Principal's Work Motivation on the Performance of Elementary School Teachers in Gunungwungkal District - Hariyasasti, Yayuk (Journal of Industrial Engineering & Management Research, 2025)
This study aims to describe and analyze (1) The influence of transformational leadership of principals on teacher performance in elementary schools throughout Gunugwungkal District, (2) The influence of principal's work motivation on teacher performance in elementary schools throughout Gunugwungkal District. The research method used is quantitative descriptive through a survey. Data were collected through questionnaires distributed to 56 elementary school teachers in Gunugwungkal District which were determined using the simpler random sampling method, research data were obtained by distributing online questionnaires through social media. Data were analyzed using structural equation modeling (SEM). The results of the study indicate that there is a positive and significant influence between transformational leadership and teacher performance and principal's work motivation has a significant influence on teacher performance.